Chemically Addressable Perovskite Nanocrystals for Light‐Emitting Applications. Issue 34 (10th July 2017) - Sun, Haizhu; Yang, Zhenyu; Wei, Mingyang; Sun, Wei; Li, Xiyan; Ye, Shuyang; Zhao, Yongbiao; Tan, Hairen; Kynaston, Emily L.; Schon, Tyler B.; Yan, Han; Lu, Zheng‐Hong; et al.
Abstract : Whereas organic–inorganic hybrid perovskite nanocrystals (PNCs) have remarkable potential in the development of optoelectronic materials, their relatively poor chemical and colloidal stability undermines their performance in optoelectronic devices. Herein, this issue is addressed by passivating PNCs with a class of chemically addressable ligands. The robust ligands effectively protect the PNC surfaces, enhance PNC solution processability, and can be chemically addressed by thermally induced crosslinking or radical‐induced polymerization. This thin polymer shield further enhances the photoluminescence quantum yields by removing surface trap states. Crosslinked methylammonium lead bromide (MAPbBr3 ) PNCs are applied as active materials to build light‐emitting diodes that have low turn‐on voltages and achieve a record luminance of over 7000 cd m −2, around threefold better than previous reported MA‐based PNC devices. These results indicate the great potential of this ligand passivation approach for long lifespan, highly efficient PNC light emitters. Abstract : A new approach to enhance perovskite nanocrystal (PNC) stability is developed through a class of intrinsically crosslinkable ligands. These ligands provide an opportunity for crosslinking between PNCs, which effectively improves the material stability and photoluminescent properties. The application of these crosslinked PNCs in light‐emitting diodes is successfully achieved, demonstrating the importance that ligand design has on PNC stability and device performance.